Visualisasi Kehilangan Ibu Berdasarkan Lagu “Fourth Of July” (Oleh Sufjan Stevens) pada Koleksi Fashion - Aninidta, Alifia Putri (Universitas Negeri Surabaya, 2024)
In a family, the figure of the mother generally plays a very large role. Mothers are the most influential figures in shaping children's psychology, personality and morals. The statement sparked a question.